Bi/Zn Dual Single‐Atom Catalysts for Electroreduction of CO2 to Syngas. Issue 7 (17th February 2022) - Meng, Lingzhe; Zhang, Erhuan; Peng, Haoyu; Wang, Yu; Wang, Dingsheng; Rong, Hongpan; Zhang, Jiatao
Abstract: The electrochemical CO2 reduction reaction to produce CO is one of the most promising pathways to eliminate CO2 emissions and store intermittent energy sources. However, the most critical usage of CO is via mixing with H2 to form syngas, which is a crucial feedstock for many value‐added chemicals. Therefore, producing syngas with a suitable CO/H2 ratio in a one‐step reaction is desirable in the CO2 RR process. To achieve this end, dual single‐atom sites supported by the nitrogen‐doped carbon show great potential. Herein, we show that a dual single‐atom catalyst with Bi−N4 and Zn−N4 units is efficient for generating syngas with tunable CO/H2 ratios (0.20 to 2.92), which is of great significance to downstream industrial production. Moreover, this work highlights the potential to control the CO/H2 ratios for efficient syngas production using the coexisting single‐atom sites. Abstract : Fischer‐Tropsch : Bi/Zn dual single‐atom catalysts (BiZn/NCs) were prepared by a gas‐migration/NH3 ‐mediated strategy. The BiZn/NCs catalyzed the electroreduction of CO2 to syngas with the controllable CO/H2 ratios from 0.20 to 2.92, suitable for an efficient Fischer‐Tropsch process. We found the pyridinic‐N−Bi/Zn bonding had a great impact on the electrocatalytic performances.